Analysis of the Judgment of the Judge in the Settlement of Default Agreement Debts (Case Study Decision Number 515/Pdt.G/2020/PN.Jkt.Sel) - Shafaa Alaadini Yuan; Gunawan Djajaputra (Journal of Law, Politic and Humanities, 2024)
Analysis of Judges' Considerations in Settling Defaults in Debt Agreement (Case Study of Decision Number 515/Pdt.G/2020/PN.Jkt.Sel) aims to examine how judges assess default cases and reflect relevant civil law principles. This research uses a normative legal method with a statutory approach. The results showed that in the decision, the judge considered the authentic deed of acknowledgment of debt made by the defendant as valid evidence of the agreement between the plaintiff and the defendant. Although the defendant acknowledged the debt, the judge found that the defendant did not fulfill its obligation to pay, which was considered a default. The judge also emphasized the importance of good faith in the execution of the agreement, asserting that the collateral in the form of land certificates provided by the defendant did not change the fact that the obligation had not been fulfilled. Finally, the judge granted the plaintiff's claim, affirming the protection of violated rights and demonstrating a commitment to upholding justice in the legal system. This decision reflects the application of fundamental civil law principles, emphasizing the importance of authentic deeds, the definition of default, and the need to comply with agreed obligations. Through careful analysis of evidence and enforcement of creditors' rights, this decision not only resolves the dispute but also educates the public on civil law, encouraging integrity and compliance in transactions